Warm Inflation with Nonminimal Derivative Coupling - Kourosh Nozari; M. Shoukrani; N. Rashidi (Advances in High Energy Physics)
We study the effects of the nonminimal derivative coupling on the dissipative dynamics of the warm inflation where the scalar field is nonminimally coupled to gravity via its kinetic term. We present a detailed calculation of the cosmological perturbations in this setup. We use the recent observational data from the joint data set of WMAP9 + BAO + H0 and also the Planck satellite data to constrain our model parameters for natural and chaotic inflation potentials. We study also the levels of non-Gaussianity in this warm inflation model and we confront the result with recent observational data from the Planck satellite.